Poultry manure nitrogen availability influences winter wheat yield and yield components - Savala, C.E.N.; Crozier, C.R.; Smyth, T.J. (Wiley, 2016)
Standard poultry manure use recommendations in North Carolina consider waste analysis but not differences among manure types, cropping seasons, or application timing. This study evaluated poultry manure source, N rate strategy, and application time effects on soft red winter wheat (Triticum aestivum L.) tiller density, yield components, grain yield, and N availability coefficients. Coefficients included fertilizer N equivalence based on grain yield and plant-available N based on aboveground plant N content. Four field experiments used broiler litter (BL) and composted layer manure (CLM), two rates (67 and 134 kg total-N ha−1), and three different application times (incorporated in October preplant, Feekes’ 3 in December/January, or Feekes’ 4 in February). Dual-source treatments received 67 kg N ha−1 of manure plus 67 kg N ha−1 as urea ammonium nitrate (UAN) solution at Feekes’ 5. Fertilizer-N (UAN) rate treatments (0, 39, 78, 117, and 156 kg N ha−1) were also included. Yields responded to N inputs but were lowest when BL and CLM were applied at 67 kg N ha−1 either preplant or at Feekes’ 3. Grain yield and N availability were greater with CLM than with BL (3.0 vs. 2.8 t ha−1 grain and 58 vs. 52 kg ha−1 N uptake, respectively). Availability coefficients ranged from 12 to 32%, lower than the standard assumed values of 50 to 60%. The feasible poultry manure application window includes preplant until Feekes’ 4, but fertilizing winter wheat crops solely with poultry manure may supply less N than intended.